The Relationship Between Parenting Styles and Mental Health Among Adolescents at SMP Negeri 4 Denpasar - I Gusti Ayu Dian Sari Dewi; M. Adreng Pamungkas; Kiki Rizki Fista Andriana (Jurnal Medicare, 2026)
Adolescent mental health is an important issue because adolescence is a developmental stage that is vulnerable to psychological disorders. This study aims to identify parenting styles, describe mental health conditions, and analyze the relationship between parenting styles and adolescent mental health at SMP Negeri 4 Denpasar. The research used a quantitative cross-sectional design with a sample of 190 students. The instruments utilized were a parenting style questionnaire and a mental health assessment. Data were analyzed using the Spearman correlation test. The results showed that most parents applied a permissive parenting style, with 111 respondents (58.4%), and a majority of students were in the at-risk mental health category, with 94 respondents (49.5%). The Spearman rank test produced a p-value of 0.014 and an r-value of 0.178, indicating a significant relationship between parenting style and mental health among adolescents at SMP Negeri 4 Denpasar, although the strength of the correlation was very weak. This study highlights the importance of appropriate parenting in supporting adolescent mental health and the need for psychological support interventions in schools